Advance care planning in rural New South Wales from the perspective of general practice registrars and recently fellowed general practitioners. (28th June 2019) - Littlewood, Jean; Hinchcliff, Reece; Lo, Winston; Rhee, Joel
Abstract: Objective: This study examined advance care planning as delivered by general practice registrars and recently fellowed GPs in New South Wales rural settings. The facilitators and barriers to advance care planning uptake in these areas were investigated, as well as the state of general practice training on advance care planning. Design: Qualitative descriptive methodology, involving semi‐structured face‐to‐face and telephone interviews. Setting: Primary care. Participants: General practice registrars and recently fellowed GPs in New South Wales rural settings. Definition of rural using the Australian Standard Geographical Classification ‐ Remoteness Area. Thirteen participants were included in the study. Main outcome measures: Thematic analysis of interview transcripts elucidated key issues emerging from participants' accounts. Results: Key barriers included doctor‐dependent uptake, demands on doctor's time and the limited relevant resources available. Facilitators recognised were patient control in end‐of‐life care and long‐standing relationships between GPs and their patients. Uptake among patients was low, and minimal training on advance care planning reported. Conclusion: The lack of training opportunities in advance care planning during vocational training, especially when combined with the essential role played by rural GPs in initiating advance care planning and providing end‐of‐life care, appears to be a major problem that might contribute to poor uptake among patients in rural areas. This study demonstrated, however, the significant benefits that advance care planning could bring in patients living in rural communities if delivered effectively. Given that rural GPs face a number of barriers to providing routine health care, these results highlight an important need to provide GPs and rural communities with support, education, incentive, better administrative tools, options and greater awareness of advance care planning.